Regulatory mechanisms of Th9 cell differentiation - Liu, Xingyue; Li, Ya; Wu, Wenwen; Huang, Han; Hao, Yanmei; Song, Chuanwang (Frontiers in Immunology, 2025)
Th9 cells, a distinct subset of T helper cells, are defined by their production of IL-9. Th9 cells play a role in the development of various diseases by participating in mucosal immune responses, defending tissue barriers, and regulating inflammatory responses. For instance, Th9 cells contribute to inflammatory bowel disease by secreting IL-9, which damages the intestinal epithelial barrier. The effects mediated by Th9-derived IL-9 exhibit environment-dependent characteristics. In allergic asthma, IL-9 drives inflammation, while in specific tumor microenvironments, IL-9 can exert anti-tumor effects. Th9 cell differentiation is governed by a complex, multi-layered regulatory network. This network centers on the synergistic action of transforming growth factor-beta (TGF-β) and interleukin-4 (IL-4). Additionally, it involves multiple other mechanisms. These include exogenous signals such as IL-2 and IL-35; intrinsic transcription factors like the ATF-like protein BATF and PU.1; epigenetic modifications, including histone acetylation and DNA methylation; and metabolic reprogramming, such as glycolysis and lipid metabolism, among others. This review systematically summarizes the regulatory mechanisms governing Th9 cell differentiation. It elucidates these mechanisms and reveals potential therapeutic targets, including transcription factors such as PU.1, IRF4, and BATF. This work paves the way for the development of Th9-related immunotherapies.